Associations between national financial trends and facial plastic surgery procedural volume. (11th October 2019) - Gadkaree, Shekhar K.; McCarty, Justin C.; Weitzman, Rachel E.; Derakhshan, Adeeb; Mohan, Suresh; Bergmark, Regan W.; Shaye, David A.
Abstract : Objective(s): To characterize procedural trends in facial plastic and reconstructive surgery procedures in relation to the United States economy. Methods: Retrospective cohort study examining annual procedure rates were determined from the American Society of Plastic Surgeons (ASPS) National Clearinghouse of Plastic Surgery Procedural Statistics from January 1 2007 to December 30, 2017. Procedures were compared to economic activity of the United States as measured by gross domestic product (GDP) were compared using Kolmogorov‐Smirnov goodness of fit testing and piecewise multivariate regression modeling. Results: Annual trends in procedural rates showed an overall decrease in the rates of rhinoplasty (284, 960 to 218, 924), blepharoplasty (240, 660 to 209, 571), and otoplasty (28, 571 to 23, 433) from 2007 to 2017. Total cosmetic surgery remained fairly stable, while minimally invasive cosmetic surgery increased in frequency over the study period. On piecewise regression analysis, rhinoplasty ( P = .02), rhytidectomy ( P = .007), invasive cosmetic surgery ( P < .001) were significantly associated with GDP, whereas otoplasty ( P = .98) and reconstructive surgery ( P = .11) were not associated with GDP. Conclusion: Cosmetic plastic surgery procedures show a greater correlation to GDP than reconstructive procedures. Trends in plastic surgery cases over the last decade show a decreasing number of rhinoplasty, otoplasty, and blepharoplasty, with stabilization in the last few years. An increasing number of reconstructive cases are found. Level of Evidence: 4 Laryngoscope, 130:632–636, 2020